4-Vinylcyclohexene diepoxide disrupts sperm characteristics, endocrine balance and redox status in testes and epididymis of rats. (2nd November 2017) - Adedara, Isaac A.; Abolaji, Amos O.; Ladipo, Emmanuel O.; Fatunmibi, Ore J.; Abajingin, Ayodeji O.; Farombi, Ebenezer O.
ABSTRACT: Objectives: Exposure to 4-vinylcyclohexene diepoxide (VCD) was reported to induce testicular germ cell toxicity in rodents. However, there is paucity of information on the precise biochemical and molecular mechanisms of VCD-induced male reproductive toxicity. Methodology: This study investigated the influence of VCD on testicular and epidydimal functions following oral exposure of Wistar rats to VCD at 0, 100, 250 and 500 mg/kg for 28 consecutive days. Results: Administration of VCD significantly decreased the body weight gain and organo-somatic indices of the testes and epididymis. When compared with the control, VCD significantly decreased superoxide dismutase and catalase activities in the testes whereas it significantly decreased superoxide dismutase activity but increased catalase activity in the epididymis. Moreover, while glutathione peroxidase activity and glutathione level remain unaffected, exposure of rats to VCD significantly increased glutathione S-transferase activity as well as hydrogen peroxide and malondialdehyde levels in testes and epididymis of the treated rats. The spermiogram of VCD-treated rats showed significant decrease in epididymal sperm count, sperm progressive motility, testicular sperm number and daily sperm production when compared with the control. Administration of VCD significantly decreased circulatory concentrations of follicle-stimulating hormone, luteinizing hormone and testosterone along with testicular and epididymal degeneration in the treated rats. Immunohistochemical analysis showed significantly increased cyclooxygenase-2, inducible nitric oxide synthase, caspase-9 and caspase-3 protein expressions in the testes of VCD-treated rats. Conclusion: Exposure to VCD induces testicular and epidydimal dysfunctions via endocrine suppression, disruption of antioxidant enzymes activities, increase in biomarkers of oxidative stress, inflammation and apoptosis in rats.